Interrupted irrigation and synchronism of reproductive bud development in organic and high density coffee trees (Coffee arabica L.) - Marques do Nascimento, Luís; da Silva Oliveira, Carlos Alberto; Lopes Silva, Cícero (Coffee Science - ISSN 1984-3909, 2011)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif]-->This work assessed the impact of interrupted irrigation on the synchronism of reproductive bud development in coffee after pruning of the primary lateral branches and the tree top. The water regimes were: no irrigation; irrigation all year round; irrigation interrupted after 30 days and 15 days before harvesting; and during harvesting for IAPAR 59 and Obatã cultivars. The treatments without irrigation and with irrigation all year around reduced the number of flowers and buds. Interrupted irrigation treatments improved the synchronism of coffee bud development. IAPAR 59 and Obatã cultivars provided different results, depending on the studied variable.